Calling for New Scholarly Inquiry: The Imperative for Research on Faith-Based Approaches to Experiential Learning - Green, Patrick (Experiential Learning and Teaching in Higher Education, 2025)
In this current socio-political moment—marked by increasing polarization, questions of institutional identity, and renewed attention to values- and faith-based educational experiences—a denominational perspective offers a unique lens through which to examine the role of experiential learning.